2013
DOI: 10.3390/nu5020579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Malnutrition on the Expression of Cytokines Involved in Th1 Cell Differentiation

Abstract: Malnutrition is a common cause of secondary immune deficiency and has been linked to an increased susceptibility to infection in humans. Malnutrition specifically affects T-cell-mediated immune responses. The aim of this study was to assess in lymphocytes from malnourished children the expression levels of IL-12, IL-18 and IL-21, molecules that induce the differentiation of T cells related to the immunological cellular response (Th1 response) and the production of cytokines related to the immunological cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 24 publications
3
44
0
Order By: Relevance
“…Malnutrition is a common cause of secondary immune deficiency, and previous studies characterizing cytokine changes showed reductions in IL2 (17, 18, 38) and IFNγ (18, 19) with inconsistent reductions in IL1 (38–40) and increases in IL10 (15, 17, 38) and TNF-α (17, 39). Compared with reference ranges (33, 4144), >50% of patients in our cohort had higher cytokine concentrations for GCSF, IL10, IL12p40, macrophage inflammatory protein 1α, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malnutrition is a common cause of secondary immune deficiency, and previous studies characterizing cytokine changes showed reductions in IL2 (17, 18, 38) and IFNγ (18, 19) with inconsistent reductions in IL1 (38–40) and increases in IL10 (15, 17, 38) and TNF-α (17, 39). Compared with reference ranges (33, 4144), >50% of patients in our cohort had higher cytokine concentrations for GCSF, IL10, IL12p40, macrophage inflammatory protein 1α, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal function and inflammation in SAM may be modulated by short-chain fatty acids (SCFAs), which are fermentation byproducts produced by the intestinal microflora and are an important energy source for intestinal epithelial cells (1114). Malnutrition is also associated with altered systemic immune responses, such as abnormal proinflammatory priming (15, 16) decreased regulatory cytokines, and impaired immune activation (1719). …”
Section: Introductionmentioning
confidence: 99%
“…The adequate intake of nutrients is essential for organs and systems to function properly; this includes the immune system, whose performance is critical to effectively protect the body against pathogens 6,7.…”
Section: Introductionmentioning
confidence: 99%
“…Since nutritional deficiencies can lead to immune system dysfunction 7,32, we infer that malnourished patients are more likely to suffer from immunoparalysis. Thus, interventional studies have been performed using nutrient supplementation to reverse this condition </emph>32,33.…”
Section: Introductionmentioning
confidence: 99%
“…As immunity to TB is mediated by protective T cells, these vaccines employ a range of adjuvants or live-delivery systems to promote protective T cells (reviewed in references 13 and 14). However, the cellular part of the immune system has, in early studies, been reported to be sensitive to the effects of PEM (15,16), resulting in reduced production of the T helper type 1 (Th1) cytokines gamma interferon (IFN-␥) and interleukin-2 (IL-2) (17)(18)(19)(20). The cellular and molecular background of this reduced response is not fully understood and has been the subject of some debate (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%